2022
DOI: 10.1111/cea.14139
|View full text |Cite
|
Sign up to set email alerts
|

Establishing subclasses of childhood eczema, their risk factors and prognosis

Abstract: Background The heterogeneity of development and progression of eczema suggests multiple underlying subclasses for which aetiology and prognosis may vary. A better understanding may provide a comprehensive overview of eczema development and progression in childhood. Thus, we aimed to determine longitudinal eczema subclasses based on assessments and identify their associations with risk factors and allergic outcomes. Methods A total of 619 participants with a family history of allergic disease were assessed at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
9
1
Order By: Relevance
“…An interesting RCT conducted in China in 2020 by(Cheng et al, 2020) reported that paternal education through nurses could improve the management of atopic dermatitis among children. In contrast to this study,(Lopez et al, 2022) reported different findings.Children with a family history of atopic sensitization, such as bronchial asthma, allergic rhinitis, and eczema, could be significant factors, and this will help the health care workers to provide focused health education. Our research reported that family history of bronchial asthma (OR [95% CI] = 0.71 [0.58 -0.93], p = 0.013), and family history of eczema (OR [95% CI] = 4.32 [2.61 -6.96], p= 0.001).…”
contrasting
confidence: 95%
“…An interesting RCT conducted in China in 2020 by(Cheng et al, 2020) reported that paternal education through nurses could improve the management of atopic dermatitis among children. In contrast to this study,(Lopez et al, 2022) reported different findings.Children with a family history of atopic sensitization, such as bronchial asthma, allergic rhinitis, and eczema, could be significant factors, and this will help the health care workers to provide focused health education. Our research reported that family history of bronchial asthma (OR [95% CI] = 0.71 [0.58 -0.93], p = 0.013), and family history of eczema (OR [95% CI] = 4.32 [2.61 -6.96], p= 0.001).…”
contrasting
confidence: 95%
“…Other studies also reported that persistent eczema was associated with the development of FA 19 as well as asthma and hay fever. 8,20 Further, our results suggest that, the age at eczema onset plays an important role in allergic multimorbidity. Earlier onset of eczema showed a stronger association with FA, asthma and hay fever presence, with "Very early onset" showing higher aOR's (adjusted Odds Ratio) than "Early onset" and "Late onset".…”
Section: Discussionmentioning
confidence: 52%
“…Typically, these disease phenotypes are being stratified according to age of onset, persistence and severity of AD. [7][8][9][10] Differences in underlying pathophysiological pathways which might cause this heterogeneity of AD are yet to be described. 8 However, pinpointing the phenotype at highest risk for developing allergic multimorbidity and identifying phenotype-specific risk factors is needed for developing personalized prevention and treatment strategies for children with AD.…”
Section: Introductionmentioning
confidence: 99%
“…170,171 Similarly, over the past 5 years, longitudinal data on eczema were clustered using data-driven approaches. [172][173][174][175][176][177][178][179] There were notable differences in the estimated prevalence of each phenotype, and inconsistent associations with the filaggrin (FLG) genotype.…”
Section: Heterogeneity and Endotype Discoverymentioning
confidence: 99%